Faust : a Tragedy in Two Parts. - Goethe, J. Wolfgang (Algora Publishing, 2016)
"A poet, playwright, novelist, memoirist, and aphorist, Goethe was the German equivalent of Dante plus Shakespeare, a multifaceted universal genius. He put everything he had into this version of the famous myth of Faust, the man who sold his soul to the devil for worldly fame and riches. People face such choices every day - in this volume, Prof. Thomas Wayne presents the story in a contemporary voice."--